Pengaruh Konvergensi IFRS dan Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility - Fichy Rohana; Sri Ayem (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is to determine the effect of IFRS convergence and profitability on disclosure of corporate social responsibility. This study included descriptive statistical research. The population of this research is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2013 - 2017. The samples were determined using purposive sampling. Data uses secondary data. To determine the effect of the independent variables on the dependent variable using multiple linear regression analysis. The results of this study IFRS convergence does not affect the disclosure of corporate social responsibility and profitability positively influencing disclosure of corporate social responsibility.